AN ANALYSIS OF SPEAKING ACTIVITIES IN INDONESIAN ELT TEXTBOOK BASED ON COGNITIVE DOMAIN OF BLOOM’S TAXONOMY REVISED - Inggrit Presti Rena; Abdul Kodir Al-Baekani; Acep Bahrum Kamil (IKIP Siliwangi, 2022)
Textbook has an essential role as teaching material, especially in learning speaking English. Teachers should use a suitable textbook in their teaching process to meet learning objectives. This study aims to analyze speaking activities based on cognitive domain in the Indonesian ELT textbook endorsed by Indonesian Ministry of Educational and Culture entitled Bahasa Inggris, Think Globally Act Locally untuk SMP/MTS Kelas IX [English for Junior High School Grade IX]. The data was analyzed with content analysis method and collected using documentary technique. The findings show that there were three speaking activities such as reading aloud, role play, and presentation task. Also, there were 57 speaking activities that focused on cognitive domain category. Besides, all categories of cognitive domain did not apply in this textbook. There are only four categories that were applied such as remembering (C1), applying (C3), analyzing (C4), and creating (C6). However, understanding (C2) and evaluating (C5) level categories did not realize in this textbook. Thus, this textbook was not quite good to fulfill learning objectives and the distributions of cognitive domain for the levels. Keywords: Speaking Activity, English Textbook, Cognitive Domain, Content Analysis